Determination of copper ion at trace levels in apple tea samples by simultaneous complexation and spray assisted microextraction method prior to detection by flame atomic absorption spectrophotometry - Diridiri, Paye Naz; Bodur, Sezin Erarpat; Bayraktar, Ahsen; Gunkara, Omer Tahir; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2024)
In the present study, a green and sensitive analytical method for the determination of copper ion at trace levels in apple tea samples was developed. Simultaneous complexation/extraction of the analyte were achieved by spraying-based fine droplet formation liquid-phase microextraction (SFDF-LPME). Copper ion was complexed with a Schiff base chelating agent called as N,N '-Bis(salicylidene)-1,2-phenylenediamine (BSP). Under the optimum conditions, the developed SFDF-LPME-FAAS and FAAS system were assessed with respect to limit of detection (LOD), limit of quantitation (LOQ), linearity and percent relative standard deviation (%RSD). LOD and LOQ values for SFDF-LPME-FAAS method were found to be 6.0 and 19.9 mu g/kg, respectively. Enhancement in calibration sensitivity for developed method was found as 23 folds. In addition, accuracy/suitability of the developed SFDF-LPME-FAAS method were confirmed by spiking experiments. Two different apple tea samples were spiked to different concentration values and percent recovery results from 91.1 and 123.8 % proved the accuracy/suitability of the method.
Keywords: Copper ion; Flame atomic absorption spectrophotometry; Schiff base; Spraying-based fine droplet formation liquid; phase microextraction; Apple tea; LIQUID-LIQUID MICROEXTRACTION; SOLID-PHASE EXTRACTION; DEEP EUTECTIC SOLVENT; FAAS DETERMINATION; CADMIUM; WATER; LEAD; Chemistry; Food Science & Technology; Nutrition & Dietetics